2018
DOI: 10.1186/s12966-018-0703-3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training modalities in patients with type 2 diabetes mellitus: a systematic review and network meta-analysis

Abstract: IntroductionCurrent international guidelines recommend aerobic, resistance, and combined exercises for the management of type 2 diabetes mellitus (T2DM). In our study, we conducted a network meta-analysis to assess the comparative impact of different exercise training modalities on glycemic control, cardiovascular risk factors, and weight loss in patients with T2DM.MethodsWe searched five electronic databases to identify randomized controlled trials (RCTs) that compared the differences between different exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
209
3
27

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(250 citation statements)
references
References 77 publications
11
209
3
27
Order By: Relevance
“…Thus, there is no information on the long‐term effects of an intervention using an HIIT protocol in type 2 diabetes . It is well established that a combination of aerobic exercise and resistance training (RT) is more beneficial than either alternative alone for improving glycaemic control . However, previous trials have not analysed the effectiveness of HIIT combined with RT concening health‐related variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is no information on the long‐term effects of an intervention using an HIIT protocol in type 2 diabetes . It is well established that a combination of aerobic exercise and resistance training (RT) is more beneficial than either alternative alone for improving glycaemic control . However, previous trials have not analysed the effectiveness of HIIT combined with RT concening health‐related variables.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] It is well established that a combination of aerobic exercise and resistance training (RT) is more beneficial than either alternative alone for improving glycaemic control. 7,17,18 However, previous trials have not analysed the effectiveness of HIIT combined with RT concening health-related variables. Therefore, the purpose of this one-year randomized controlled trial was to investigate the effects of HIIT or MCT combined with RT on glycaemic control, body composition, cardiorespiratory fitness (CRF) and enjoyment of physical activity in patients with type 2 diabetes.…”
mentioning
confidence: 99%
“…The statistical heterogeneity of different studies was assessed by Cochran's Q statistic and I 2 statistics, which were quantitative measures of consistency across studies. When the p value of Q test ≥ 0.10 and I 2 < 31%, the heterogeneity was considered low and, when the p < 0.10 and I 2 > 56%, the heterogeneity was considered high . In addition, when the heterogeneity was low across different studies, a fixed model was applied; in other cases, a random model was used to pool the data.…”
Section: Methodsmentioning
confidence: 99%
“…However, most published key papers are included in the WoS database, and moreover, the WoS is the most commonly used database in bibliometrics analysis (9,10). Secondly, all datasets were identified using computer software or tool, such as VOSviewer, CiteSpace, and WoS, rather than being selected and collected manually, and manual selection and collection of datasets is required for systematic reviews or overviews (36)(37)(38)(39)(40); therefore, these datasets may be subject to bias (e.g., irrelevant studies may be included), although this would not affect the trends identified and conclusions of the present study. Finally, data generated from studies published in the current year (2019) were not included in our analysis as the dataset for this year is incomplete.…”
Section: Strengths and Limitationsmentioning
confidence: 99%